Tissue culture, cellular behaviour and pigment analysis of Agapanthus Praecox Ssp. Minimus / Jamilah Syafawati Yaacob - Yaacob, Jamilah Syafawati (2013)
In vitro regeneration and somatic embryogenesis of Agapanthus praecox ssp. minimus were successfully achieved in this study from three types of explants (leaf, root and bulb) that were cultured on MS (Murashige and Skoog, 1962) media supplemented with various hormones at different concentrations and on plant growth regulator-free MS media as control. Bulb explant was identified as the most responsive explant for direct regeneration of A. praecox ssp. minimus, while leaf and root explants failed to produce any shoots or roots. In contrast, both leaf and root explants were found to be very responsive in callus induction and production of somatic embryos, while bulb explants were the least responsive. Micropropagation of A. praecox was best achieved when bulb explants were cultured on MS media supplemented with 2.0 mg/L IBA and 2.0 mg/L Kinetin with mean number of shoots per explant of 4.50 ± 0.38, where 90.00 ± 5.57 % of the explant (bulb) samples had produced shoots. On the other hand, production of roots was best achieved through addition of 1.0 mg/L IBA and 1.0 mg/L Kinetin, with mean number of roots per explant of 4.47 ± 0.30. However, the use of plant growth regulator-free MS media failed to produce any shoots or roots from all the three explant types. Callus induction was successfully obtained from all explant types, depending on the different types of plant growth regulators being used. Induction of callus from bulb explants of A. praecox was only achieved from cultures supplemented with 2,4-D. The best plant hormone for induction of callus was also identified, where it was found that 2.0 mg/L PIC and 2.0 mg/L 2,4-D had produced the highest dry weight of callus from leaf and root explants, with dry weight of callus of 0.410 ± 0.003 g and 0.600 ± 0.002 g, respectively. The produced callus was subjected to double staining method to distinguish embryogenic callus from non-embryogenic callus. It was found that root explants were the most responsive for induction of somatic embryogenesis, where 52.38% from a total of 21 hormone combinations had yielded somatic embryogenic callus. Leaf explants of A. praecox also produced embryogenic callus when supplemented with various plant hormones except TDZ and Picloram (when the cultures were maintained in the dark). Regeneration of complete plantlets was achieved through transfer of somatic embryos onto plant growth regulator-free MS medium. Successful acclimatization of in vitro grown A. praecox ssp. minimus plantlets was observed from all growth substrates tested, with varied degree of response. Combination of red soil and black soil at a ratio of 1:1 was found to be the best growth substrate for A. praecox spp. minimus, in contrast to red soil, with survival rates of 96.67 ± 3.33 % and 73.33 ± 8.21 %, respectively. This study also depicted the importance of initial morphological features prior to acclimatization of the in vitro plantlets. It was shown that initial morphological features of the plantlets largely influenced the growth and survival of the plantlets, where it was found that plantlets with more leaves and taller in height performed better than that with initially fewer leaves and shorter in height. However, no obvious morphological abnormalities were observed visually or through scanning electron microscope (SEM), indicating no occurrence of somaclonal variation, as attested by cytological studies conducted on root meristem cells of in vivo and in vitro (with and without 1 mg/L IBA and 1 mg/L Kinetin) grown A. praecox. The chromosome number of A. praecox was observed to be constant (30) in all samples, despite the addition of hormones to the growth media. However, the size of the nucleus and meristematic cells were found to be decreasing when cultured in vitro and with prolonged culture time. Similar observations were noted for ploidy levels of A. praecox, where prolonged culture time was found to induce the occurrence of ployploid cells. The beautiful violet-blue colour of A. praecox flower petals was also exploited for production of natural colourant. The coloured pigment was identified as anthocyanin, as determined through pH variation tests and UV-visible spectrophotometry. The production of natural colourant was achieved by mixing the extract with Poly (methyl methacrylate) (PMMA) resin (1:1 ratio of extract : resin) and tested via weathering tests to assess the durability of the produced colourant. Both salt and heating tests revealed that the colour of the coating did not fade (but became darker) with increasing temperatures. The surface of the coated glass slide was observed to be even and shiny upon application of the produced colourant and no surface cracks were observed with increasing temperatures except with extreme heat (at 100 °C), which rarely occurs in nature.